2021
DOI: 10.3390/medicina57090904
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study on the Use of the “Monocyte-Rich” Platelet-Rich Plasma in Combination with 1927 nm Fractional and 308 nm Excimer Lasers for the Treatment of Vitiligo

Abstract: Background and objectives: Vitiligo is an acquired chronic and idiopathic skin disorder, characterized by selective loss of melanocytes and resulting in a cutaneous depigmentation. Treatment for vitiligo remains a challenge for dermatologists; thus, it is frustrating both for physicians and patients. The objective of this study was to evaluate a combination treatment characterized by the use of a leukocyte-rich platelet-rich plasma, which is particularly rich in monocytes (defined here as monocyte-rich PRP), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Platelet-rich plasma has been reported as a valuable adjuvant tool to narrowband UVB phototherapy, excimer laser and fractional laser in treatment of vitiligo [5][6][7][8] and vitiligo surgery. [9][10][11] However, the value of PRP in treatment of knowingly resistant sites has not been adequately evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelet-rich plasma has been reported as a valuable adjuvant tool to narrowband UVB phototherapy, excimer laser and fractional laser in treatment of vitiligo [5][6][7][8] and vitiligo surgery. [9][10][11] However, the value of PRP in treatment of knowingly resistant sites has not been adequately evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…3 There are different types of platelet-rich plasma (PRP) including pure platelet-rich plasma (P-PRP), leukocyte and platelet-rich plasma (L-PRP), pure platelet-rich fibrin and leukocyte and platelet-rich fibrin (L-PRF). 4 Plateletrich plasma has been reported to enhance the repigmentation response of different therapeutic modalities for vitiligo, including narrowband UVB phototherapy, excimer laser and fractional laser [5][6][7][8] as well as vitiligo surgery via enhancing melanocyte proliferation and boosting hair growth and hair melanocyte reservoir. [9][10][11] Platelet-rich plasma offers further advantages in vitiligo surgery as it contains trypsin inhibitor, which can enhance melanocyte survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 PRP contains growth factors, chemokines, cytokines and other plasma proteins that inhibit local inflammatory responses and promote melanocyte regeneration. 33 Khattab et al 34 and Mercuri et al 35 demonstrated that PRP combined with 308-nm EL is feasible for vitiligo. So far, there is no single treatment that completely cures vitiligo, so we hope to have more novel combination therapies, such as PRP in combination with 308-nm EL, available for clinicians and patients to choose from in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, platelets can also release numerous anti-inflammatory cytokines such as interleukin-1 receptor antagonist (IL-1ra), soluble tumor necrosis factor (TNF) receptor (sTNF-R) I, interleukin (IL)-4, IL-10, IL-13, and interferon γ [ 73 ]. PRP has been used as an autologous injection for various medical conditions to promote healing and tissue regeneration/rejuvenation [ 73 , 74 , 75 , 76 , 77 , 78 ]. Additionally, PRP has also been used widely in alopecia treatment due to its ability to induce cell proliferation, supporting HF growth, and extending anagen [ 72 , 79 , 80 , 81 , 82 ].…”
Section: Cia Treatmentmentioning
confidence: 99%